Investigating clotting changes in intracerebral haemorrhage patients from Steve Biko Academic Hospital by studying the viscoelastic and ultrastructural properties of platelet-poor plasma - Bester, Janette (University of Pretoria, 2025)
Dissertation (MSc (Human Physiology))--University of Pretoria, 2024.